Active labour market policy vs employment tax credits: lessons from recent UK reforms - Richard Blundell; Costas Meghir (Institute for Labour Market Policy Evaluation (IFAU), 2002)
Many welfare-to-work programs in both North America and Europe are directed at making work pay for the low skilled. This paper identifies two alternative policies that are motivated by this same objective active labour market programs that involve wage subsidies together with improved job matching; and earned income tax credits that supplement wages for working low-income families. Although sharing similar concerns over labour market incentives for low skilled workers, these alternative policies typically differ in many important ways. We present an evaluation of the impacts of two such recent programs designed to enhance the labour market attachment of low-wage workers in the UK. These programs have many features in common and are similar to many policy proposals in Europe and North America. The evaluation of the UK reforms brings empirical evidence into the debate on the effectiveness of these programs and is used to assess what aspects of their design work well and what aspects could be improved.
Keywords: C25; H31; H53; J21; J22; 330; welfare reform; tax credits; wage subsidies; labour supply